Give me liberty or give me money: the fiscal decentralization and autonomy of regional governance in Slovakia - Jaroslav Mihaĺik; Peter Horvat́h; Martin Svikruha (European Journal of Government and Economics (EJGE), 2019)
The aim of this study is to focus on fiscal decentralization and regional financial autonomy in Slovakia. The public administration reform and fiscal decentralization process in Slovakia ought to increase the autonomy of the multi-level governance and to decrease its dependency on state budgeting and other transfers. We argue that regional territorial governance is greatly dependent on financial incentives from central state financing, which limits the expected effect of decentralization and regional fiscal autonomy. By collecting quantitative data on state transfers and revenues to regional governments we demonstrate the limits of spatial, financial and decision-making autonomy within particular regions. The selected time frame 2005-2016 reflects all stages, reforms and changes in the fiscal decentralization of the second level governance in Slovakia.
Keywords: 330; fiscal decentralization; fiscal autonomy; regional governance; Slovakia